Optimal Capital Structure and Financial Performance Analysis for PT Matahari Department Store Tbk - Halim, Maggie Rosalina; Sukarno, Subiakto (Journal of Business and Management, 2015)
Abstract. PT. Matahari Department Store Tbk has been doing an aggressive expansion by keeps expanding its network and opening up new stores. From this year onward the company has determined 74 possible locations for new stores. To support expansion plan above, the company needs to achieve better financial performance as share price of company is influenced by the company’s performance. To maximize share price and company’s value, the management will need to increase the performance and fix aspect that is still lacking. Other than that to do the expansion efficiently, optimal capital structure will be needed. To analyze the company financial performance, the author uses time series and cross sectional analysis, while to find the optimal capital structure the author will use WACC method. The analysis indicates that the current capital structure of PT. Matahari Department Store Tbk consists of 80% debt and 20% equity. The optimal capital structure for PT. Matahari Department Store Tbk is in 68% of debt level. For financial performances, there are some aspects that already ideal and some are not yet ideal.